1981
DOI: 10.1111/j.1469-8137.1981.tb04568.x
|View full text |Cite
|
Sign up to set email alerts
|

Amylose in Floridean Starch

Abstract: S U M M A R Y Previous reports, based on studies involving approximately 10 genera of the higher red algae, have concluded that floridean starch is composed of arnylopectin only. Our investigations on seven members of the Porphyridiales and a member of the Bangiales (Erythrocludiu) have demonstrated conclusively the presence of amylose in red algal starch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 4 publications
0
15
0
1
Order By: Relevance
“…Red algae were first thought to accumulate starch devoid of amylose in the cytoplasm. The presence of amylose was, however, relatively recently reported for a number of unicellular red algae, including Rhodella violacea (26). Older reports characterizing the structure of starch in cryptophytes and dinoflagellates clearly mention the presence of amylose in these polysaccharides (1,2,34).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Red algae were first thought to accumulate starch devoid of amylose in the cytoplasm. The presence of amylose was, however, relatively recently reported for a number of unicellular red algae, including Rhodella violacea (26). Older reports characterizing the structure of starch in cryptophytes and dinoflagellates clearly mention the presence of amylose in these polysaccharides (1,2,34).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, at first this material was shown to lack amylose, the minor polysaccharide fraction of starch that contains fewer than 1% ␣-1,6 linkages (for reviews concerning starch structure and amylose synthesis, see references 4 and 8). It was later found that some unicellular red algae did accumulate amylose within their floridean starch granules (26).…”
mentioning
confidence: 99%
“…Nevertheless, the absence of amylose fraction does not appear to define a universal feature of floridean starch. Extended survey of floridean starch composition highlights the presence of a significant amylose fraction in the genus Porphyridiales (McCracken and Cain 1981;Shimonaga et al 2007). Floridean starch defines a semicrystalline polysaccharide whose crystallinity ranges from 16 to 36 % depending on red alga species (Shimonaga et al 2008).…”
Section: Starch Metabolism and Structure In Rhodophyceaementioning
confidence: 99%
“…Зеленые водоросли запасают углеводы в виде крахмала (амилозы), у Rhodophyta запасным углеводом является флоридский крахмал (амилопектин), а бурые водоросли накапливают глюкозный полисахарид ламинарин (Roberts, Whelan, 1960;Chesters, Bull, 1963;McCracken, Cain, 1981;Zemke-White, Clements, 1999). Известно, что фермент амилаза может разрушать амилозу и амилопектин, а ламинариназа расщепляет ламинарин до простых сахаров и, прежде всего, глюкозы (Roberts, Whelan, 1960;Chesters, Bull, 1963).…”
unclassified